A Photovoice Study on the Position and Role of Hospice Volunteers in Korea - Lee S; Kim B (Dove Medical Press, 2023)
Sowon Lee, Boyoung Kim College of Nursing, Chonnam National University, Gwangju, South KoreaCorrespondence: Boyoung Kim, College of Nursing, Chonnam National University, 160 Baekseo-ro, Dong-gu, Gwangju, 61469, South Korea, Tel +82-62-530-4936, Fax +82-62-220-4544, Email bkimjhu@gmail.comPurpose: As the quality of life increases, so does the demand for a dignified life. Although there is an increasing interest in hospice care, which helps people experience a comfortable death, the level of change in perception and in its role remain insignificant.Methods: This study investigated the position and role of hospice care using photovoice, a technique used in Participatory Action Research, to analyze the data collected from hospice volunteers who participated in a training program in Korea.Results: The participants viewed hospice volunteering from the two perspectives: facing unexpected farewells and supporting like bicycle training wheels, highlighting the role of the "connection between death, life, and rest" as a mediator in conflicts between the patients and medical staff. Although the participants dreaded hospice volunteering, it prepared them to share their lives and provided an opportunity for inner growth by expanding knowledge through learning and establishing a "meaningful connection with the community" because they volunteered out of love, not obligation.Conclusion: Because the demand for hospice and palliative care is increasing, this study is meaningful as it investigates the perception of hospice care and determines its influencing factors based on the perspective of hospice volunteers and the changes in their perception over time.Keywords: hospice, volunteer, position, role, photovoice